Structural characterization of rhamnogalacturonan domains from Panax ginseng C. A. Meyer. (1st January 2019) - Sun, Lin; Ropartz, David; Cui, Liangnan; Shi, Huimin; Ralet, Marie-Christine; Zhou, Yifa
Highlights: RG-I and RG-II domains were isolated from ginseng and structurally characterized. Ginseng RG-I contained arabinan, galactan and AG-II as side chains. Both low-branched and high-branched side chains linked to ginseng RG-I backbone. RG-II domain in ginseng root was first isolated and analyzed. Abstract: Rhamnogalacturonan I (RG-I) and rhamnogalacturonan II (RG-II) domains were isolated from ginseng pectin by alkali saponification and endo-polygalacturonase hydrolysis, then purified by anion-exchange and size-exclusion chromatography. Monoclonal antibody detection indicated that ginseng RG-I contained →4)-α-GalpA-(1→2)-α-Rhap-(1→ repeating units as backbone, with arabinan, galactan and type II arabinogalactan (AG-II) as side chains. The use of galactose- and arabinose-releasing enzymes, mass spectrometry analysis of the oligosaccharides generated by rhamnogalacturonan hydrolase, and glycosidic linkage analyses provided evidence that ginseng RG-I contains both single galactose-branched subunits and highly branched subunits with arabinan and AG-II side chains. RG-II was analyzed by sequential acid hydrolysis followed by mass spectrometry. Ginseng RG-II contains 9 galacturonic acid units as backbone. Side chain A is an octasaccharide with 0 ∼ 1 methyl ether group. Side chain B is a nonasaccharide with 0 ∼ 1 acetyl group. These results provide useful information for further investigation of structure-activity relationship of ginseng pectin.